Revolusi Industri 4.0 Menurut Klaus Schwab: Dampak dan Tantangannya bagi Kehidupan Manusia Dewasa Ini - Finsenzo Frano Savsavubun; Barnabas Ohoiwutun (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2023)
Klaus Schwab is a German development engineer and economist. He is known as the founder and executive chairman of the world economic forum. His study focused more on economic development. His encounter with Ferdinand Piech at the Swiss Federal Institute of Technology in Zurich further strengthened Klaus Schwab's enthusiasm and attention to the world economy. For Schwab, we are at the beginning of a revolution that has been fundamentally changed the way we live, the way we work and relate to others. These new changes occur on the basis of the development of the latest technologies. The focus of this study is to discuss on the industrial revolution 4.0 according to Klaus Schwab. With the method of description and analysis, this article seeks to explain Scwhab’s notion of industrial revolution, its impacts and challenges, and at the same time indicating efforts and attitudes to respond to and deal with the challenges that occur.